FORMATION OF PROFESSIONAL COMPETENCE OF FUTURE TEACHERS IN THE COURSE OF STUDYING THE DISCIPLINE "INNOVATIVE TECHNOLOGIES OF TEACHING MATHEMATICS AND COMPUTER SCIENCE" - Тягай, Ірина; Махомета, Тетяна (Modern engineering and innovative technologies, 2024)
The article describes the peculiarities of forming the professional competence of a future teacher in the course of studying the discipline "Innovative Technologies for Teaching Mathematics and Informatics". A modern teacher should have a broad outlook on